Comparative Study of Dual-Stator Permanent Magnet Machines with Different PM Arrangements and Rotor Topologies for Aviation Electric Propulsion - Minchen Zhu; Lijian Wu; Dongliang Liu; Yiming Shen; Rongdeng Li; Hui Wen (Machines)
The dual-stator permanent magnet (DSPM) machine has proved to have high space utilization and a redundant structure, which can be beneficial to improving the fault tolerance and torque density performance. In this paper, three types of DSPM machines are proposed and compared, where two sets of armature windings are wound in both inner/outer stators, producing more than one torque component compared with single-stator PM machines. The machine topology and operating principle of three DSPM machines are analyzed first. Next, feasible stator/rotor-pole number combinations are compared and determined. Furthermore, based on the finite-element (FE) method, both the electromagnetic performances of three DSPM machines under open-circuit and rated-load conditions after optimization are compared, aimed at generating maximum torque at fixed copper loss. The FE analyses indicate that the dual-stator consequent-pole permanent magnet (DSCPPM) machine generates maximum torque per PM volume, together with relatively high efficiency, which makes it a potentially hopeful candidate for low-speed and high-torque applications. In addition, a thermal analysis is carried out to confirm the validity of the design scheme. Finally, in order to verify the FE predictions, a prototype DSCPPM machine is manufactured and experimentally tested.